FILSAFAT KARAKTER KRISTEN: Diskursus Dialog Analogis dan Konfirmasi Biblika - Paparang, Stenly Reinal (STT Injili Indonesia Medan, 2024)
Character is an important subject in discussions about faith, philosophy, and morals. Character itself occupies the space of human life which is realized in the form of humanity relations, moral ethics, and spirituality. The decline of character is a serious phenomenon and challenge in the Christian faith. In some cases, ministers of God fall into the sin of adultery, even displaying bad character in certain actions. It appears that faith and deeds are discrepant and discursive. This fact has created wounds of spirituality and trust in the church. Through a descriptive approach, this study aims to elaborate a Christian philosophy of character that presents an analogous dialogue of views on character in relation to morals, spirituality, and human relations, and states biblical confirmation. The results of this study show that: first, Christian character rests on the juxtaposition of the law of love introduced by God for His people; second, Christian character applies the principle of imitating Christ; and third, Christian character is bound to an eschatological portrait that becomes the foundation for looking forward to His return.